Gut microbiota involved in desulfation of sulfated progesterone metabolites: A potential regulation pathway of maternal bile acid homeostasis during pregnancy - Wang, Peng; Chen, Qianqian; Yuan, Peiqiang; Lin, Sen; Chen, Hong; Li, Ran; Zhang, Xiaoling; Zhuo, Yong; Li, Jian; Che, Lianqiang; Feng, Bin; Lin, Yan; et al. (Frontiers in Microbiology, 2022)
Abnormally raised circulating bile acids (BA) during pregnancy threat fetal and offspring health. Our previous study has identified sulfated progesterone metabolites (PMSs) in part account for dysregulation of maternal BA metabolism during pregnancy, however, limited intervention strategies to remedy increased serum BA through PMSs during pregnancy are available. The purpose of this study is to test the feasibility of manipulating BA homeostasis and progesterone metabolism through steering gut microbiota. A total of nineteen pregnant sows were randomly treated with standard diet or vancomycin-supplemented diet, to investigate the intercorrelation of PMSs, intestinal microbiota, and maternal BA metabolism from day 60 of gestation (G60) until farrowing (L0). Pregnant mice orally gavaged with epiallopregnanolone sulfate (PM5S) or vehicle and nonpregnant mice were sampled and further analysed to verify the effect of PM5S on maternal BA metabolism. The present study revealed that oral vancomycin reduced maternal fasting serum total BA (TBA) levels and postprandial serum TBA levels at day 90 of gestation (G90). BA profile analysis showed the decreased TBA after vancomycin treatment was attributed to the decrease of primary BA and secondary BA, especially hyodeoxycholic acid (HDCA). By using newly developed UPLC-MS/MS methods, we found vancomycin increased fecal excretion of allopregnanolone sulfate (PM4S) and PM5S during late gestation and thus maintaining the relative stability of serum PM4S and PM5S, which play an important role in BA metabolism. Further study in mice showed that pregnant mice have higher serum and liver TBA levels compared with nonpregnant mice, and PM5S administration induced higher gallbladder TBA levels and TBA pool in pregnant mice. In addition, after oral vancomycin, the continuously decreased Parabacteroides genus, potentially enriched with genes encoding steroids sulfatase, may explain the increased fecal PMSs excretion in pregnant sows. Taken together, our study provides the evidence that pregnancy-induced elevation of BA levels in sow is likely regulated by manipulation of gut microbiota, which offer new insights into the prevention and treatment of disrupted BA homeostasis during pregnancy by targeting specific microbiota.